10.4k views
2 votes
How many solutions does the system have? {y=−3x+5y=x^2−3x+5 Enter your answer in the box

User CAD
by
5.6k points

2 Answers

6 votes

Answer:

There are 2 solutions

Explanation:

Given the 2 equations

y = 3x + 5 → (1)

y = x² - 3x + 5 → (2)

Substitute y = x² - 3x + 5 into (1)

x² - 3x + 5 = 3x + 5 ← Subtract 3x + 5 from both sides

x² - 6x = 0 ← factor out x from each term

x(x - 6) = 0

Equate each factor to zero and solve for x

x = 0

x - 6 = 0 ⇒ x = 6

Substitute these values into (1) for corresponding values of y

x = 0 : y = 0 + 5 = 5 ⇒ (0, 5) ← is a solution

x = 6 : y = (3 × 6) + 5 = 18 + 5 = 23 ⇒ (6, 23) ← is a solution

User Tiffiny
by
5.5k points
3 votes
ANSWER

One solution,

(0,5)

EXPLANATION

The given expression:


y = - 3x + 5

and


y = {x}^(2) - 3x + 5

We equate the two equations to get,


{x}^(2) - 3x + 5 = - 3x + 5

This implies that,


{x}^(2) - 3x + 3x + 5 - 5 = 0


{x}^(2) = 0


x = 0

We put this value of x into any of the equations to get,


y = - 3(0) + 5


y = 5

The system has only one solution,

(0,5).
User Minimalpop
by
5.3k points